2004
DOI: 10.1271/bbb.68.1449
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of theL-Lysine Biosynthetic Pathway in the Obligate MethylotrophMethylophilus methylotrophus

Abstract: The L-lysine biosynthetic pathway of the gramnegative obligate methylotroph Methylophilus methylotrophus AS1 was examined through characterization of the enzymes aspartokinase (AK), aspartsemialdehyde dehydrogenase, dihydrodipicolinate synthase (DDPS), dihydrodipicolinate reductase, and diaminopimelate decarboxylase. The AK was inhibited by L-threonine and by a combination of L-threonine and L-lysine, but not by L-lysine alone, and the activity of DDPS was moderately reduced by L-lysine. In an L-lysine produci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…8) We attempted to obtain the threonine auxotrophs for the purpose of avoiding feedback inhibition of aspartokinase by threonine. Petek et al have reported that decreasing biomass might allow increased precursor supply from central metabolism into the L-lysine biosynthetic pathway by minimizing the loss of carbon required for cell growth.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8) We attempted to obtain the threonine auxotrophs for the purpose of avoiding feedback inhibition of aspartokinase by threonine. Petek et al have reported that decreasing biomass might allow increased precursor supply from central metabolism into the L-lysine biosynthetic pathway by minimizing the loss of carbon required for cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…M. methylotrophus strains were grown on a modified minreral salts medium (SEIIa) at 37 C in test tubes and flasks. 8) Streptomycin (50 mg/l) was used to maintain plasmid pSEA10 in M. methylotrophus.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells of M. methylotrophus AS1 were grown at 37°C on a mineral medium SEIIa (Gunji et al 2004) O, 9.7 mg/l, methanol 2%, pH 7.0. Bactoagar (1.2%, Difco, USA) and methanol 1% were applied to the solid media.…”
Section: Methodsmentioning
confidence: 99%